PLUNC Proteins Positivity in Patients with Chronic Rhinosinusitis: A Case-Control Study. (15th July 2014) - Passali, Desiderio; Sarafoleanu, Codrut; Manea, Claudiu; Loglisci, Michele; Passali, Francesco Maria; Cambi, Jacopo; Iosif, Cristina; Panaitescu, Eugenia; Bellussi, Luisa Maria
Abstract : Introduction . Innate immunity is the first protection against microorganisms. Nowadays, there is a growing interest in innate immune molecule known as palate, lung, nasal epithelial clone (PLUNC). PLUNC is a specific product of the airways, of approximately 25 kDa, encoded by adjacent genes found within a 300 kb region of chromosome 20; these proteins must be detected predominantly in the upper respiratory tract. Materials and Methods . We performed a case-control study to investigate the presence of this protein in nasal tissue of patients affected by chronic rhinosinusitis. 59 patients were enrolled (44 cases, 15 controls). We have examined the correlation between the presence of pathology and the PLUNC proteins positivity. Results . 100% of controls have a +++ rated PLUNC proteins positivity, while cases have a lower percentage of positivity. We used χ 2 statistical test to analyze the results of the study and there is a difference statistically significant between cases and controls in PLUNC proteins positivity. Conclusions . These observations suggest that, in response to agents or chemical factors, nasal mucosal epithelium will react and produce PLUNC proteins. So PLUNC proteins have a protective function on upper airways mucosa, as we can see by evaluating the high positivity in control group.